Research on control strategy for energy management of hydrogen-electric hybrid vehicles in urban rail transit applications based on fuzzy control - LI Hongwei; CHEN Limei; GAO Yang; WANG Jian; SHI Lei; XIANG Weiran (机车电传动)
The hydrogen-electric hybrid has emerged as the most promising power source for the transformation and upgrading of rail transit owing to its high efficiency and zero carbon emission. In this context, control strategies aimed at efficient energy management are crucial for improving the economic efficiency and service life of such hybrid power systems. This paper presented a hybrid power model specifically developed for urban rail transit vehicles, which was established based on the power and energy requirements of typical vehicles used in urban and suburban traffic. This model incorporated a fuzzy logic control strategy for energy allocation. Moreover, a trapezoidal membership function and the Mamdani fuzzy inference method were employed for fuzzy processing. Simulation results show that hybrid power urban rail vehicles utilizing an energy management strategy based on fuzzy control effectively balance train power demands, the output characteristics among fuel cell systems, and supercapacitor systems, and achieve improved fuel economy and system efficiency through real-time adjustments of energy allocation. Compared with the traditional power supply mode using OCS systems, the proposed strategy improves vehicle efficiency by about 25.36%, and demonstrates significant energy-saving effects, while remaining the optimal power range without abrupt changes in fuel cell power output.